A case report on delayed diagnosis of perforated Crohn's disease with recurrent intra-psoas abscess requiring omental patch. (2019) - Gao, David; Medina, Melissa G.; Alameer, Ehab; Nitz, Jonathan; Tsoraides, Steven
Highlights: Psoas muscle abscess can be misdiagnosed for other etiologies, such as appendicitis. The current management of a Crohn's abscess is debated. Treatment is influenced by abscess size, quantity of abscesses, and response to antibiotics and/or percutaneous drainage. Our patient, whose abscess was managed with the novel use of omental packing, has not demonstrated abscess recurrence. Abstract: Introduction: Intra-abdominal abscesses associated with Crohn's disease (CD) can rarely occur in the psoas muscle. An intra-psoas abscess is prone to misdiagnosis because its location mimics other diseases, like appendicitis and diverticulitis [1 ]. Presentation of case: We present the case of a 25-year-old female with an 11-year history of CD, previously well-controlled on Remicade, who presented with right lower quadrant (RLQ) pain and CT findings of a right psoas abscess initially attributed to perforated appendicitis. Two percutaneous drainages pre-ileocecectomy, laparoscopic ileocecectomy, three percutaneous drainages post-ileocolectomy, and evidence of a recurrent abscess prompted diagnostic laparoscopy. The abscess was unroofed and debrided. A flap of omentum was used to fill the abscess cavity. A comprehensive literature search was performed using the terms 'Crohn's abscess', 'intra-psoas abscess', and 'omental patches' in Medline and on PubMed. Discussion: We attribute the abscess' recurrence to possible epithelialization of the abscess cavity. Intra-psoas abscesses, albeit rare, are a known manifestation of CD. Percutaneous drainage is the initial standard of care, although diagnosis can be difficult given its association with several diseases, which can delay definitive treatment. We summarize a recently proposed and agreed upon treatment scheme for the management of the Crohn's patient with an abdominal abscess. We also propose the novel technique of omental packing in abscess management. Conclusion: Clinician awareness must be heightened for perforating CD in the setting of abscess refractory to either multiple drainage procedures, although care should be taken to individualize treatment to each CD patient who presents with an abdominal abscess.